(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2026)
Transmission and distribution networks represent the most extensive part of electric power systems, making them more susceptible to faults. This necessitates protecting these networks to reduce damages to the equipment and ensure the stability of the power system. One of the most important types of protection used in transmission lines is distance protection, which relies on impedance algorithms to calculate the fault location. This paper addresses the design and implementation of a digital distance protection algorithm for overhead transmission lines in power networks using an Arduino microcontroller, making it suitable for small-scale power systems and educational purposes. The impedance is calculated digitally to determine the fault location, utilising accurate algorithms to enhance response and speed up fault isolation. The algorithm implementation is based on the differential approximation method to reduce errors caused by the effects of harmonics and the DC component. The work stages included system simulation using MATLAB Simulink, and on the practical side, the design and implementation of voltage and current measurement circuits and signal conditioning circuits, in addition to programming the Arduino microcontroller. The system’s performance was tested practically on a laboratory transmission line from LabVolt, and the results showed good accuracy in the simulation and the system’s applicability to real-world implementation